Letters to a Young Pharmacist : Even More Sage Advice on Life and Career. - Cantrell, Susan A.; White, Sara J.; Scott, Bruce E. (Paris : American Society of Health-System Pharmacists, 2022)
Letters to a Young Pharmacist is the next installment of the ASHP Letters series created to inspire pharmacists through all stages of their professional journey.
LACT_710928_proof -- LACT_710929_proof -- LACT_710930_proof -- LACT_710931_proof -- LACT_710932_proof -- LACT_710933_proof -- LACT_710934_proof -- LACT_710935_proof -- LACT_710936_proof
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Pharmacy -- Vocational guidance; Pharmacists -- United States -- Correspondence; Pharmacie -- Orientation professionnelle; Pharmaciens -- États-Unis -- Correspondance; Pharmacists; Pharmacy -- Vocational guidance; United States; Personal correspondence